Designing a Clinical Decision Support System (CDSS) for the Implementation of INA-CBGs - Pradita, Riska; Putri, Widya; -, Rahmawati (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2023)
The implementation of the INA-CBG system still faces several challenges, including the discrepancy between actual hospital costs and INA-CBG costs. These challenges can be minimized using a comprehensive information system. A Clinical Decision Support System is a system designed to support practitioner decision-making in the clinical management of patients, including the implementation of INA-CBGs. The purpose of this study is to design a CDSS for the implementation of INA-CBGs. This research uses a qualitative method with an Action Research approach divided into four stages, namely (1) Diagnosing Action by identifying challenges and analyzing user needs related to features, databases and display design, (2) Planning Action is carried out by designing Flowcharts, Use Case Diagrams, Entity Relationship Diagrams, Data Flow Diagrams and Prototypes, (3) Taking Action is carried out by designing interface designs using figma which can be accessed via the link https://bit.ly/EvaluasiSistemCDSS and (4) Evaluation which shows the CDSS System score in the implementation of INA-CBG's obtained from the evaluation is above the average global SUS score of 75 and it can be said that the CDSS system in the implementation of INA-CBG's can be accepted by users as a system that can help users in controlling costs.